The Mistakes of Super Powers in Afghanistan - Salangi, Mohammad Mullah (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
Afghanistan’s strategic location and lying at the crossroad linking the Central Asian States with South Asian region motivated major powers to take interest and competing with each other for the purpose of dominance. This paved the way for making Afghanistan battleground of different powers. So, Afghanistan is a country with a myriad history inflicted with conflicts of interests among regional and international powers. Therefore, Afghanistan has a deep history of insurgency, resistance and wars that shapes the perceptions of the people who live there. For instance, Taliban propaganda portrayed Afghanistan’s President Hamid Karzai as an American Shah Shuja, a cutting reference to the king the British brought to power in 1839 during the First Anglo-Afghan War (1839-42). When British troops deployed to southern Afghanistan in 2006, residents feared they had been sent to take revenge for the Afghan victory at the Battle of Maiwand which took place there during the Second Anglo-Afghan War in 1880. In addition, plans for withdrawing international forces from Afghanistan, immediately make Afghans recall the Soviet withdrawal in 1989 that began a slide to civil war. However, the super powers interferences in the internal affairs (cultural and religious values) of the Afghans lead to wars and political turmoil so much so that the country cannot be turned to a stable state. The paper examines the mistakes of major powers and their destruction role in the continuing civil war and miserable situations of the Afghan people.